Vascular Collagen Type-IV in Hypertension and Cerebral Small Vessel Disease. Issue 12 (7th October 2022) - Kumar, Apoorva A.; Yeo, Natalie; Whittaker, Max; Attra, Priya; Barrick, Thomas R.; Bridges, Leslie R.; Dickson, Dennis W.; Esiri, Margaret M.; Farris, Chad W.; Graham, Delyth; Lin, Wen Lang; Meijles, Daniel N.; et al.
Abstract : Background: Cerebral small vessel disease (SVD) is common in older people and causes lacunar stroke and vascular cognitive impairment. Risk factors include old age, hypertension and variants in the genes COL4A1/COL4A2 encoding collagen alpha-1(IV) and alpha-2(IV), here termed collagen-IV, which are core components of the basement membrane. We tested the hypothesis that increased vascular collagen-IV associates with clinical hypertension and with SVD in older persons and with chronic hypertension in young and aged primates and genetically hypertensive rats. Methods: We quantified vascular collagen-IV immunolabeling in small arteries in a cohort of older persons with minimal Alzheimer pathology (N=52; 21F/31M, age 82.8±6.95 years). We also studied archive tissue from young (age range 6.2–8.3 years) and older (17.0–22.7 years) primates ( M mulatta ) and compared chronically hypertensive animals (18 months aortic stenosis) with normotensives. We also compared genetically hypertensive and normotensive rats (aged 10–12 months). Results: Collagen-IV immunolabeling in cerebral small arteries of older persons was negatively associated with radiological SVD severity (ρ: −0.427, P =0.005) but was not related to history of hypertension. General linear models confirmed the negative association of lower collagen-IV with radiological SVD ( P <0.017), including age as a covariate and either clinical hypertension ( P <0.030) or neuropathological SVD diagnosis ( P <0.022) as fixed factors. Reduced vascular collagen-IV was accompanied by accumulation of fibrillar collagens (types I and III) as indicated by immunogold electron microscopy. In young and aged primates, brain collagen-IV was elevated in older normotensive relative to young normotensive animals ( P =0.029) but was not associated with hypertension. Genetically hypertensive rats did not differ from normotensive rats in terms of arterial collagen-IV. Conclusions: Our cross-species data provide novel insight into sporadic SVD pathogenesis, supporting insufficient (rather than excessive) arterial collagen-IV in SVD, accompanied by matrix remodeling with elevated fibrillar collagen deposition. They also indicate that hypertension, a major risk factor for SVD, does not act by causing accumulation of brain vascular collagen-IV.